Conceptual and Theoretical Approaches to Corporate Social Responsibility, Entrepreneurial Orientation, and Financial Performance - Paiva, I.; Carvalho, L. (2020)
Over the past few years, we have witnessed the enormous success of corporate social responsibility in businesses all over the world. In particular, we have seen an international scenario in which governments foster both growth through entrepreneurship and achievement of sustainable development, by creating tools such as UN Global Compact for worldwide impact in order to reconcile business interests with the demands of communities. The impact of corporate social responsibility at national and international level has been unequivocal in the creation of jobs and wealth, and new solutions for development have been enabled. While not ignoring these important developments in corporate social responsibility, our main goal is to fully unleash the broad potential of corporate social responsibility, entrepreneurship, and firm’s performance activity, exploring and highlighting new trends in this area. There is currently an extensive literature addressing the main topics on corporate social responsibility; however, the extant research has a focus which is too limited compared to the wide diversity of corporate social responsibility in business. Corporate social responsibility and entrepreneurship is a new sub-area of entrepreneurship profiled as one of the concepts that, in conjunction with business strategy, can redirect organizational performance research in new directions. In addition, with the same goal of improving performance, some authors point out the suitability of adopting this type of multiple strategic orientation. This book focuses on new trends of corporate social responsibility from the entrepreneurial point of view and on firm performance. Specifically, in this area, we are called to change our approach towards a long-term growth, replacing the short-term vision which had come to be adopted in recent times.